Tantangan dalam Kegiatan Literasi Media di Indonesia - Bobi Guntarto (Ultimacomm: Jurnal Ilmu Komunikasi, 2016)
he advancement of communication media and technology requires audience to have the knowledge and skill of media literacy for them to use the media in an appropriate way. For that purpose, media literacy trainings with various forms, materials and purposes, have been done frequently in many areas of Indonesia. This research aims to find the relation between the goals of media literacy training and important aspects in media literacy skill. This research uses qualitative approach with descriptive analysis. The result shows that many media literacy trainings in Indonesia have not been consistent in adjusting the goals and the essential aspects of media literacy skill. It means the conceptual understanding and study of media literacy have not adequately performed by the activists. It is expected that the result of this study could encourage similar research by elaborating theory and concept of media literacy which can be used to develop the curriculum of media literacy training program. This study also encourages media literacy programs with better goals, forms and materials. Keywords: Media literacy, media literacy training model, media literacy in Indonesia